EFFORT TO FULFILL THE RIGHT TO WOMEN'S REPRODUCTIVE HEALTH IN INDONESIA'S STATE LAW SYSTEM - Fatimah, Utari Dewi; Tuti Rastuti (Pasundan International of Community Services Journal (PICS-J), 2024)
The high maternal mortality rate (MMR) is one of the indicators to determine the health status of women. In addition, MMR is one of the main targets that have been determined by WHO as an indicator of a country's health. The fulfillment of the right to women's reproductive health can be realized in the Indonesian legal state system, through legal marriage (Article 28B paragraph (1) of the 1945 Constitution). Efforts are being made to fulfill it, namely by improving maternal health, providing health service facilities as needed, low reproductive health, especially for women, will have an impact on the babies they are born. The research was done using normative juridic method. Based on the findings gathered from secondary research result and supported by primary result, it shows that reproductive health is a basic right of every person, so guaranteeing the availability of health facilities and infrastructure is a medium to guarantee and protect so that people can enjoy these basic rights. The form of this research is descriptive analytical and analyzed using normative juridical methods. Reproductive health aims to ensure the fulfillment of the reproductive rights of everyone, including women, through quality, safe, and accountable health services, as well as ensuring maternal health in reproductive age so that they are able to give birth to healthy and quality generations and reduce maternal mortality.